Indirect treatment comparison of lanadelumab and a C1-esterase inhibitor in pediatric patients with hereditary angioedema - Maureen Watt; Rachel Goldgrub; Mia Malmenas; Katrin Haeussler (Journal of Comparative Effectiveness Research)
Aim: To compare the efficacy and safety of lanadelumab versus other approved long-term prophylaxis (LTP) treatments in patients with pediatric hereditary angioedema (HAE) aged <12 years. Materials & methods: A systematic literature review was conducted to identify studies of LTP in patients with HAE aged <12 years. Two studies met the inclusion criteria in an indirect treatment comparison of efficacy and safety data in pediatric HAE patients. These were for lanadelumab (SPRING, NCT04070326) and intravenous-C1-esterase inhibitor (C1-INH[IV], NCT02052141). A propensity score analysis used individual patient-level data from both studies in a logistic regression model to estimate inverse probability weights. To avoid convergence issues and an underpowered analysis due to the small sample size (n = 29), the base case was defined as Poisson regression analyses on monthly attack rate adjusting for one covariate (baseline attack rate). Model selection among unadjusted, adjusted and weighted regression models was conducted through the Akaike and Bayesian Information Criteria. Results: Lanadelumab 150 mg every 2 weeks (Q2W) reduced the monthly HAE attack rate by 82.1% versus C1-INH(IV) 1000 IU twice weekly (every 3–4 days [BIW]; rate ratio [RR], 0.1792 [95% CI: 0.0296–1.0853]) and by 88.9% versus C1-INH(IV) 500 IU BIW (RR: 0.1107 [95% CI: 0.0234–0.5239]). Treatment with lanadelumab Q2W reduced the risk of total adverse events by 56.2% versus C1-INH(IV) 1000 IU BIW (RR:0.4377 [95% CI: 0.1536–1.2469]) and by 66.0% versus C1-INH(IV) 500 IU BIW (RR: 0.3401 [95% CI: 0.1234–0.9371]). Conclusion: This exploratory analysis suggested a trend toward greater efficacy and fewer adverse events with lanadelumab 150 mg Q2W compared with C1-INH(IV) BIW 1000 IU and 500 IU in pediatric patients with HAE. Future studies could potentially assess larger samples over longer periods of time for the long-term preventative efficacy, safety and tolerability of lanadelumab and C1-INH(IV).